Performance of Hybrid Layers and Native Hens under Farmers` Management in a Selected Area of Bangladesh - Ershad, S.M.E. (International Journal of Poultry Science, 2005)
An experiment was conducted in Jessore district of Bangladesh during the period from January 2003 to December 2004 to investigate the performance of Brown Shelled Hybrid Layer, White Shelled Hybrid Layer and Native Hen measured during only laying period (57 weeks). 8 Brown Shelled Hybrid Layer farms, 8 White Shelled Hybrid Layer farms and 10 Native Hen farms were reared intensive, intensive and scavenging systems respectively. Result revealed that the egg production, egg weight, final body weight, feed consumption, shell weight, age at first laying, feed cost, management cost, and net profit varied significantly due to different birds and different management system. Under intensive system Hybrid Layer rearing were better than Native Hen showed moderate performance in terms of higher egg production, higher weight of egg, higher body weight and lower mortality. Feed conversion efficiency, production number of eggs, egg mass, net profit and survivability was higher in White Shelled Hybrid Layers than Brown Shelled Hybrid Layers under intensive system. Under scavenging system NH was better also for the rural area of Bangladesh, because of lower production cost, higher market price of eggs, live bird price and good profit. Rural poultry plays a vital role in the existing farming systems of Bangladesh. It can be recommended here that the Native Hen farming under scavenging system without any investment and White Shelled Hybrid Layer or Brown Shelled Hybrid Layer i.e. any one under intensive system farming are obvious for efficient and profitable egg production in Bangladesh.